2020
DOI: 10.21037/jgo.2019.10.03
|View full text |Cite
|
Sign up to set email alerts
|

Is my life going to change?—a review of quality of life after rectal resection

Abstract: Rectal resection is a common practice for colorectal surgeons. The causes of this procedure are varied. The most frequent is cancer, but also inflammatory bowel disease, endometriosis, and rectovaginal or rectourethral fistulas. The loss of the normal rectal reservoir function, urinary problems, sexual dysfunction or pelvic pain are frequently reported in patients after rectal surgery and these disorders markedly affect the overall quality of life (QoL). In the last decades, rectal surgery has radically change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 103 publications
3
17
0
Order By: Relevance
“…While there is growing literature on the psychosocial impact of young‐onset cancer, prior work focused on cancer diagnosis in general and did not delve adequately into the unique challenges of specific types of cancer. For CRC in particular, patients may experience sexual dysfunction, urinary problems and loss of normal bowel function after undergoing rectal resection 12 . Some patients may also require an ostomy, a surgically created opening to allow discharge of waste from body, which can negatively impact body image 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is growing literature on the psychosocial impact of young‐onset cancer, prior work focused on cancer diagnosis in general and did not delve adequately into the unique challenges of specific types of cancer. For CRC in particular, patients may experience sexual dysfunction, urinary problems and loss of normal bowel function after undergoing rectal resection 12 . Some patients may also require an ostomy, a surgically created opening to allow discharge of waste from body, which can negatively impact body image 13 .…”
Section: Introductionmentioning
confidence: 99%
“…For CRC in particular, patients may experience sexual dysfunction, urinary problems and loss of normal bowel function after undergoing rectal resection. 12 Some patients may also require an ostomy, a surgically created opening to allow discharge of waste from body, which can negatively impact body image. 13 Given that the incidence of young‐onset CRC continues to rise worldwide, there is a need to better understand the psychosocial impact of this specific disease in younger adults.…”
Section: Introductionmentioning
confidence: 99%
“…This may offer hope for functional outcomes of lower tumours, which are otherwise operable only with APR (29). Some studies have, however reported an increase postoperative anorectal disfunction, when combined with PCRT (30). Another confounding factor, could be the surgical donuts themselves, as a negative stapler donut does not preclude involvement of the distal margin, as it contains only a part of a staple or suture line.…”
Section: Discussionmentioning
confidence: 99%
“…With a worldwide perspective, the incidence and mortality rates of rectal cancer do not correlate but seem to depend on the availability of centers with high-volume expertise and a multidisciplinary team of clinicians guiding the course of treatment. In experienced centers, superior outcomes can be achieved shifting the focus of interdisciplinary treatment efforts toward quality-of-life and functional outcomes [3].…”
Section: Introduction: Rectal Cancer Treatment In 2022mentioning
confidence: 99%